Off-target effects of tribendimidine, tribendimidine plus ivermectin, tribendimidine plus oxantel-pamoate, and albendazole plus oxantel-pamoate on the human gut microbiota. Issue 3 (December 2018) - Schneeberger, Pierre H.H.; Coulibaly, Jean T.; Gueuning, Morgan; Moser, Wendelin; Coburn, Bryan; Frey, Jürg E.; Keiser, Jennifer
Abstract: Soil-transmitted helminths infect 1.5 billion people worldwide. Treatment with anthelminthics is the key intervention but interactions between anthelminthic agents and the gut microbiota have not yet been studied. In this study, the effects of four anthelminthic drugs and combinations (tribendimidine, tribendimidine plus ivermectin, tribendimidine plus oxantel-pamoate, and albendazole plus oxantel-pamoate) on the gut microbiota were assessed. From each hookworm infected adolescent, one stool sample was collected prior to treatment, 24 h post-treatment and 3 weeks post-treatment, and a total of 144 stool samples were analyzed. The gut bacterial composition was analyzed using 16S rRNA gene sequencing. Tribendimidine given alone or together with oxantel-pamoate, and the combination of albendazole and oxantel pamoate were not associated with any major changes in the taxonomic composition of the gut microbiota in this population, at both the short-term post-treatment (24 h) and long-term post-treatment (3 weeks) periods. A high abundance of the bacterial phylum Bacteroidetes was observed following administration of tribendimidine plus ivermectin 24 h after treatment, due predominantly to difference in abundance of the families Prevotellaceae and Candidatus homeothermaceae . This effect is transient and disappears three weeks after treatment. Higher abundance of Bacteroidetes predicts an increase in metabolic pathways involved in the synthesis of B vitamins. This study highlights a strong relationship between tribendimidine and ivermectin administration and the gut microbiota and additional studies assessing the functional aspects as well as potential health-associated outcomes of these interactions are required. Graphical abstract: Image 1 Highlights: Tribendimidine in combination with ivermectin modulate the gut microbiota. Bacteroidetes phylum is more abundant 24 h after treatment. B vitamins biosynthesis pathways are over-represented 24 h post-treatment. Tribendimidine/ivermectin effect is transient and disappears within 3 weeks.